A retrospective clinical, radiographic and microbiological study of periodontal conditions of teeth with and without crowns Um estudo retrospectivo clínico, radiográfico e microbiológico das condições periodontais de dentes com e sem coroas - Marcio Dias Giollo; Patrícia Moura Valle; Sabrina Carvalho Gomes; Cassiano Kuchenbecker Rösing (Sociedade Brasileira de Pesquisa Odontológica, 2007)
The aim of this study was to evaluate retrospectively the periodontal conditions of teeth with fixed crowns that had been in place from 3 to 5 years before the study was conducted. Forty individuals were recalled for a follow-up visit. Full-mouth clinical examinations were carried out and Visible Plaque Index (VPI), Gingival Bleeding Index (GBI), Probing Pocket Depth (PPD), and clinical attachment level (CAL) were assessed in 6 sites per tooth. Parallel radiographs were also taken and blindly analyzed by a digital caliper (distance between the apex and the bone crest). BANA tests were performed. A contra-lateral sound tooth was considered the control. Mean values were obtained and Wilcoxon and paired sample t tests were used to compare the test and control sites. Crowns had a mean VPI value of 30.42% as compared to 49.17% for sound teeth. The GBI was 33.33% and 26.25% for test and control teeth respectively. Assessment of PPD revealed values of 2.30 and 2.14 mm, and assessment of CAL revealed averages of 2.02 and 1.89 mm for test and control teeth respectively. The mean values for radiographic distances were 12.73 and 13.67 mm, and for the BANA test, 67.50 and 50.00 for sound and crowned teeth, respectively. Statistically significant differences were observed for all parameters except for CAL and for the BANA test. It may be concluded that, with the methods used in the present study, crowns may be associated with more signs of inflammation, however not with periodontal breakdown. O objetivo deste estudo foi avaliar retrospectivamente as condições periodontais de pacientes com coroas fixas colocadas de 3 a 5 anos antes da realização da pesquisa. Quarenta indivíduos foram rechamados. Exames clínicos de toda a boca foram realizados avaliando-se Índice de Placa Visível (IPV), Índice de Sangramento Gengival (ISG), Profundidade de Sondagem (PS) e Nível Clínico de Inserção (NCI) em 6 sítios por dente. Radiografias paralelas foram obtidas e analisadas cegamente por paquímetro digital (distância do ápice à crista óssea). Testes BANA foram realizados. Um dente hígido contralateral foi considerado como controle. Valores médios foram obtidos e testes de Wilcoxon e t pareado foram utilizados para comparar os sítios teste e controle. Coroas apresentaram um valor médio de IPV de 30,42%, comparado com 49,17% para dentes hígidos. O ISG foi de 33,33% e 26,25% para dentes com coroas e hígidos, respectivamente. A PS revelou valores de 2,30 e 2,14 mm e a análise do NCI demonstrou médias de 2,02 e 1,89 mm para dentes teste e controle, respectivamente. Os valores médios para as distâncias radiográficas foram de 12,73 e 13,67 mm, e para o teste BANA, de 67,50 e 50,00 para dentes hígidos e com coroas, respectivamente. Diferenças estatisticamente significantes foram observadas para todos os parâmetros, exceto para NCI e para o teste BANA. Pode-se concluir que, com os métodos utilizados no presente estudo, coroas podem ser associadas a mais sinais de inflamação, entretanto não com destruição periodontal.